Preparation method of bonded permanent magnetic ferrite
By recycling strontium chloride in the bonded permanent magnet ferrite production wastewater and using the recycling solution during the spheremaking process, the problems of waste and high cost of strontium resources are solved, and efficient utilization of strontium resources and reduction of production costs are achieved.
Patent Information
- Application Number
- CN202510125381.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The concentration of strontium chloride in the sewage discharged during bonded permanent magnet ferrite production is high, resulting in waste of strontium resources and increased costs, and the prior art does not involve the recycling of strontium chloride.
By recycling the wastewater containing strontium chloride, a high concentration of strontium chloride recovery solution was obtained, and the solution was sprayed during the sphere making of strontium dense material to obtain the ball material, and finally the bonded permanent magnet ferrite was prepared through sintering and other steps.
The utilization rate of strontium resources is significantly improved, the waste of strontium resources is reduced, the production cost is reduced, and the negative impact of strontium chloride recovery solution on product performance is reduced through the optimization process.
Smart Images

Figure CN119822807A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnetic materials, and in particular to a method for preparing a bonded permanent ferrite. Background Art
[0002] Bonded permanent ferrite refers to a permanent magnet obtained by fully mixing permanent ferrite powder with some adhesives (such as rubber, thermoplastic resin or thermosetting resin), lubricants, reinforcing agents, etc., and then molding and curing. Bonded permanent ferrite makes up for the poor flexibility and plasticity of sintered permanent ferrite, and is increasingly used in industries such as motors.
[0003] Bonded permanent magnet ferrites are mostly strontium ferrites. The main raw material of strontium is strontium carbonate. The reserves of celestite, the raw ore of strontium carbonate, are not abundant in my country, and most of them are of low grade. This leads to a high proportion of strontium carbonate in the raw material cost.
[0004] The applicant found during the production process that the concentration of strontium chloride in the wastewater discharged from the production of bonded permanent ferrites can reach about 3%. After the wastewater is treated, a large amount of strontium will be present in the solid waste for harmless treatment. If this part of strontium chloride can be recycled as raw material, the cost saving effect will be very obvious for large-scale enterprises.
[0005] Patent CN202310732992.6 discloses a bonded ferrite magnetic powder for calendering and its preparation method and application. The preparation method includes the following steps: strontium carbonate, strontium chloride and iron red are fully mixed, and the material balls are obtained through ball forming treatment; the material balls are divided into first material balls and second material balls, and the two are sintered and ground independently to obtain fine-grained material balls with an average particle size of 0.2μm to 0.4μm and coarse-grained material balls with an average particle size of 1.6μm to 2.0μm; the fine-grained material balls and coarse-grained material balls are mixed in a mass ratio of 10% to 30%: 1, and annealing and surface treatment are performed in sequence after drying, and then bonded ferrite magnetic powder is obtained after drying and crushing; the surface treatment reagent includes acetylene surfactant. However, this scheme does not involve the recycling of strontium chloride. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for preparing bonded permanent magnet ferrite. The present invention recovers wastewater containing strontium chloride to obtain a high-concentration strontium chloride recovery solution, and then uses the strontium chloride recovery solution to make balls, and finally obtains bonded permanent magnet ferrite. The method of the present invention significantly improves the utilization rate of strontium resources, can effectively reduce the waste of strontium resources, and greatly reduce costs; and on this basis, the present invention further optimizes the parameters of the strontium chloride recovery solution and the preparation process of the bonded permanent magnet ferrite, thereby minimizing the negative impact of the strontium chloride recovery solution on the production and performance of the bonded permanent magnet ferrite.
[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a method for preparing bonded permanent ferrite by recovering strontium from wastewater, which comprises the following steps: a) Densifying red iron oxide and strontium carbonate to obtain a dense material.
[0008] b) The dense material is pelletized under the condition of spraying strontium chloride recovery solution to obtain ball material.
[0009] c) The ball material is sintered to obtain pre-burned ball material; the pre-burned ball material exchanges heat with cooling water in a heat exchange kiln and is broken to obtain coarse powder.
[0010] d) Wet-milling the coarse powder to obtain slurry, and then filtering, drying, tempering and cooling to obtain bonded permanent ferrite.
[0011] The invention recovers wastewater containing strontium chloride to obtain a high-concentration strontium chloride recovery solution, then sprays the strontium chloride recovery solution during the iron-strontium dense material pelletizing process to obtain a pellet material, and finally obtains a bonded permanent magnetic ferrite after a series of post-treatments such as sintering. The method of the invention fully realizes the recycling of strontium resources, can effectively reduce the waste of strontium resources, and greatly reduces costs.
[0012] During the research and development process, the present invention found that the following technical issues need to be considered when applying the strontium chloride recovery solution to the preparation of bonded permanent magnet ferrite: (1) When the strontium chloride recovery solution is used for ball making, the precipitation blockage problem and the influence of impurity metal ions on product performance need to be considered in production. The impurity metal ions are mainly sodium, magnesium, manganese, chromium and other ions (iron, calcium and other metal ions that can react in the solid phase to form a ferrite phase are not considered as impurities); (2) The influence of the strontium chloride recovery solution on the strength of the ball material; (3) The influence of the strontium chloride content of the ball material on the subsequent sintering atmosphere; (4) The influence of the strontium chloride recovery solution ball material on the strength of the sintered pre-sintered ball, and even the subsequent influence on dry grinding and fine grinding, etc. These are systematic problems.
[0013] After a series of studies, the present invention finally provides the following solutions: (1) The present invention strictly controls the temperature and pH of the strontium chloride recovery solution at 25-50° C. and pH=7-9, respectively, and strictly controls the strontium chloride concentration at 16-22wt%. The present invention finds that the problem of precipitation blockage can be effectively solved by controlling the temperature and pH of the strontium chloride recovery solution within the above range; the temperature of the strontium chloride recovery solution should not be too high, which will not only cause heat waste, but also reduce the strength of the ball material; if the pH is too low, strontium carbonate is easy to decompose, resulting in insufficient strength of the ball material and easy disintegration; on the contrary, if the pH is too high, free strontium ions, calcium ions, etc. in the strontium chloride recovery solution are easy to precipitate and block the spray port (most of the prior art uses tap water to make balls, or uses a solution prepared by pure additives to make balls, so there is no need to consider the precipitation problem of impurity metal elements in the scheme of the present invention); in addition, when the concentration of impurity ions in the wastewater is too high, the impurities and strontium chloride content are controlled by diluting or supplementing strontium chloride at the same time.
[0014] (2) The present invention controls the moisture content of the ball material to 10-15wt%; at the same time, the diameter is controlled to 8-20mm, and the volume difference of the ball material does not exceed 20%. The present invention finds that limiting the diameter of the ball material obtained by ball making to the above range can make the ball material have higher strength; in the scheme of the present invention, in addition to considering the uniformity of the inside and outside of the conventional sintered solid phase reaction ball, the size of the ball material diameter also needs to consider the influence of strontium chloride. If the ball material diameter is too large, the ball strength will decrease. If the ball material diameter is too small, the contact surface area will be too large, which will lead to the deterioration of the atmosphere between the balls. As mentioned above, the introduction of a large amount of chloride ions and the deterioration of the atmosphere between the balls will lead to poor performance. Controlling the moisture content of the ball material to 10-15wt% can ensure the uniformity of strontium chloride in the ball material. In the scheme of the present invention, the moisture content of the ball material will not only affect the strength of the ball material in the drying section of the sintering device (rotary kiln), the adhesion between the ball material and the kiln wall, and the ball material, but also affect the molar ratio of iron to strontium in the ball material. If the moisture content is too high, it means that the strontium chloride content is too high and the iron-strontium molar ratio is low. If the moisture content is too low, it means the opposite, which will lead to large fluctuations in material performance. The bonded permanent magnet ferrite prepared by the present invention can achieve or even surpass the performance of products directly produced by strontium chloride dry method or wet method, thanks to the comprehensive control of the moisture content of the ball material, the concentration of the strontium chloride recovery solution and the pH, so that the distribution of strontium chloride in the ball material is more uniform.
[0015] (3) The present invention controls the sintering conditions to an oxygen concentration of 16-22%, an air flow rate of 5-8 m / s, a temperature of 1100-1200°C, and a time of 60-120 min. The present invention has found that controlling the oxygen content and air flow rate during sintering within the above conditions can effectively improve product performance (in conventional production, iron red chloride ions are monitored indicators, and excessive chloride ions will lead to performance deviations, while the method of the present invention introduces a large amount of chloride ions, so the atmosphere conditions are more demanding).
[0016] Preferably, in step a), the molar ratio of iron to strontium in the iron oxide red and strontium carbonate is 5.0-5.8:1.
[0017] Preferably, in step a), the densification treatment is: mixing the iron oxide red and strontium carbonate by a plowshare machine and then introducing them into a dry ball mill for ball milling and densification, and the densification time is 30-120 minutes.
[0018] Preferably, in step b), the preparation method of the strontium chloride recovery solution is: 1) Wastewater containing 2-4 wt% strontium chloride is concentrated to 40-60% volume by first steam at 100-130°C to obtain concentrated liquid A and second steam at 80-100°C.
[0019] 2) The concentrated liquid A is concentrated to 20-30% volume by the second steam to obtain the concentrated liquid B and the third steam at 70-80°C.
[0020] 3) The concentrated liquid B is concentrated by the third steam to a strontium chloride concentration of 16-22 wt %, to obtain a strontium chloride recovery solution.
[0021] Preferably, step 1) is performed in a first heat exchange and concentrating device, which is heated by a first steam, which is obtained by heat exchange with the cooling water in step c); step 2) is performed in a second heat exchange and concentrating device, which is heated by a second steam; step 3) is performed in a third heat exchange and concentrating device, which is heated by a third steam.
[0022] The present invention concentrates the wastewater containing strontium chloride into a high-concentration strontium chloride recovery solution through a triple heat exchange concentration device. Among them, the steam used in the triple heat exchange concentration device is obtained by recovering the heat energy in the pre-burned balls. In conventional technology, after the pre-burned balls are cooled with cooling water, the heat energy obtained by the cooling water is only used for ordinary flushing, which is often very surplus and causes waste. In this scheme, the heat energy of the pre-burned balls is extremely high, and it is difficult to directly use this part of the heat energy. If the pre-burned balls are directly used as a heat source to concentrate the wastewater, the equipment requirements are relatively high (the ball temperature is about 900°C, and the service life of conventional metals under this temperature condition is not long and is prone to failure. If ceramics are used, impurities are easily introduced). Therefore, this scheme realizes the heat energy exchange between the pre-burned balls and cooling water through a self-modified heat exchange kiln, and is used to heat the wastewater in the form of steam, so as to realize the concentration of production wastewater and return it to production. In order to further recover heat energy more efficiently, wastewater concentration is divided into three stages of evaporation: the first stage uses the first steam generated by the heat exchange kiln for heating, and concentrates the wastewater to 40-60% of the original volume; the second stage uses the second steam generated by the first stage of wastewater concentration for heating and the hot water condensed by the first steam to concentrate the wastewater to 20-30% of the original volume; the third stage uses the third steam generated by the second stage of wastewater concentration for heating, concentrates the wastewater to the target concentration, and ensures the impurity content and temperature. This solution can reduce the pressure of the equipment, and the steam heating uniformity is good, which can ensure the uniform heating of the concentration process, and it is divided into three concentrations, which can make better use of waste heat.
[0023] Preferably, the impurity metal content in the wastewater containing 2-4wt% strontium chloride is less than 0.2wt%; and the impurity metal content in the strontium chloride recovery solution is less than 2wt%.
[0024] Too high impurity metal content will affect product performance, so it is necessary to control the impurity metal content in wastewater and strontium chloride recovery solution.
[0025] Preferably, in step c), the temperature of the pre-sintered balls is 800-1000°C.
[0026] Preferably, in step c), the average particle size of the coarse powder is 2.0-8.0 μm.
[0027] Preferably, in step d), the mass ratio of ball material to water in the wet ball milling is 6-10:1:1-1.5.
[0028] Preferably, in step d), the average particle size of the coarse powder after wet ball milling is 1.0-2.0 μm.
[0029] Preferably, in step d), the moisture content of the slurry after filter pressing is 15-25wt%, and the moisture content after drying is <0.6wt%.
[0030] Preferably, in step d), the tempering temperature is 850-950°C.
[0031] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention recovers wastewater containing strontium chloride to obtain a high-concentration strontium chloride recovery solution, and then uses the strontium chloride recovery solution to make balls, and finally obtains bonded permanent magnet ferrite. The method of the present invention significantly improves the utilization rate of strontium resources, can effectively reduce the waste of strontium resources, and can reduce the production cost of each ton of bonded permanent magnet ferrite by about 5%.
[0032] (2) The present invention reduces the negative impact of the strontium chloride recovery solution on the production and performance of the bonded permanent magnet ferrite as much as possible by further optimizing the parameters of the strontium chloride recovery solution and the preparation process of the bonded permanent magnet ferrite.
[0033] (3) The present invention fully utilizes the heat of the pre-burned balls by transforming the traditional cooling kiln into a heat exchange kiln. The heat of the pre-burned balls is converted into steam heat to evaporate the production wastewater. At the same time, the temperature of the strontium chloride recovery solution output for ball making can be guaranteed, thereby effectively improving the utilization of thermal energy and reducing the pressure of wastewater treatment discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a connection diagram of the strontium chloride concentration and recovery device.
[0035] Figure 2 This is a schematic diagram of the structure of the heat exchange kiln.
[0036] Figure 3 This is a cross-sectional diagram of a heat exchange kiln.
[0037] Figure 4 Schematic diagram of the water inlet of the segmented water-cooling component.
[0038] Figure 5 It is a schematic diagram of the structure of a single heat exchange and concentration device.
[0039] Figure 6 It is a cross-sectional schematic diagram of a single heat exchange and concentration device.
[0040] The accompanying drawings are marked as follows: 1 heat exchange kiln, 2 steam generator, 3 first heat exchange and concentrating device, 4 second heat exchange and concentrating device, 5 third heat exchange and concentrating device, 1-1 rotating bearing, 1-2 bracket, 1-3 kiln body, 1-3-1 spiral guide plate, 1-4 feed inlet, 1-5 discharge outlet, 1-6 segmented water cooling component, 1-6-1 preheating pipe section, 1-6-2 heating pipe section, 1-6-3 water inlet, 1-6-4 water inlet pipe, 1-6-5 water outlet, 3-1 wastewater chamber, 3-2 steam chamber, 3-3 wastewater inlet, 3-4 wastewater outlet, 3-5 steam inlet, 3-6 condensate outlet, 3-7 steam outlet. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the embodiments.
[0042] Overall embodiment A method for preparing a bonded permanent ferrite comprises the following steps: a) Densifying red iron oxide and strontium carbonate to obtain a dense material.
[0043] In some preferred implementation cases, the molar ratio of iron to strontium in the iron oxide red and strontium carbonate is 5.0-5.8:1.
[0044] In some preferred implementation cases, the densification treatment is to mix the iron oxide red and strontium carbonate through a plowshare machine and then introduce them into a dry ball mill for ball milling densification, and the densification time is 30-120 minutes.
[0045] In some preferred implementation cases, the purity of the iron oxide red is above 98.5 wt %; the purity of the strontium carbonate is above 97.5 wt %.
[0046] b) The dense material is pelletized under the condition of spraying strontium chloride recovery solution to obtain ball material.
[0047] In some preferred implementation cases, the concentration of the strontium chloride recovery solution is 16-22 wt%, pH=7-9, and the temperature is 25-50°C.
[0048] In some preferred implementation cases, the water content of the ball material is 10-15wt%.
[0049] In some preferred implementation cases, the diameter of the ball material is 8-20 mm, and the volume difference of the ball material does not exceed 20%.
[0050] In some preferred implementation cases, the pelletizing is performed using a pelletizing disk.
[0051] In some preferred implementation cases, the preparation method of the strontium chloride recovery solution is: 1) Wastewater containing 2-4 wt% strontium chloride is concentrated to 40-60% volume by first steam at 100-130°C to obtain concentrated liquid A and second steam at 80-100°C.
[0052] 2) The concentrated liquid A is concentrated to 20-30% volume by the second steam to obtain the concentrated liquid B and the third steam at 70-80°C.
[0053] 3) The concentrated liquid B is concentrated by the third steam to a strontium chloride concentration of 16-22 wt %, to obtain a strontium chloride recovery solution.
[0054] Further preferably, the impurity metal content in the wastewater containing 2-4wt% strontium chloride is less than 0.2wt%; and the impurity metal content in the strontium chloride recovery solution is less than 2wt%.
[0055] Further preferably, step 1) is performed in a first heat exchange and concentrating device, which is heated by a first steam, which is obtained by heat exchange with the cooling water in step c); step 2) is performed in a second heat exchange and concentrating device, which is heated by a second steam; and step 3) is performed in a third heat exchange and concentrating device, which is heated by a third steam.
[0056] c) The ball material is sintered to obtain pre-burned ball material; the pre-burned ball material exchanges heat with cooling water in a heat exchange kiln and is broken to obtain coarse powder.
[0057] In some preferred implementation cases, the sintering conditions are: oxygen concentration 16-22%, air flow rate 5-8 m / s, temperature 1100-1200° C., and time 60-120 min.
[0058] In some preferred implementation cases, the temperature of the pre-sintered balls is 800-1000°C.
[0059] In some preferred implementation cases, the average particle size of the coarse powder is 2.0-8.0 μm.
[0060] d) Wet-milling the coarse powder to obtain slurry, and then filtering, drying, tempering and cooling to obtain bonded permanent ferrite.
[0061] In some preferred implementation cases, the ball-to-material-water mass ratio in the wet ball milling is 6-10:1:1-1.5.
[0062] In some preferred implementation cases, the average particle size of the coarse powder after wet ball milling is 1.0-2.0 μm.
[0063] In some preferred implementation cases, the moisture content of the slurry after filter pressing is 15-25wt%, and the moisture content after drying is <0.6wt%.
[0064] In some preferred implementation cases, the tempering temperature is 850-950°C.
[0065] In some preferred implementation cases, the strontium chloride recovery solution is prepared by a strontium chloride concentration recovery device, which comprises: The heat exchange kiln comprises a kiln body which is arranged horizontally and can rotate by itself, with a feed inlet and a discharge outlet at the two ends of the kiln body respectively, a spiral guide plate is arranged inside the kiln body, and a segmented water cooling component is coiled on the surface of the kiln body; The steam generator has two interfaces connected to the water inlet and the water outlet of the segmented water-cooling component, respectively, to realize hot water collection and conversion into steam and supply of cooling water (to the segmented water-cooling component); The triple heat exchange and concentration device is connected to the steam generator to realize the transportation of steam to the triple heat exchange and concentration device.
[0066] In some more preferred implementation cases, the kiln body is arranged at an angle of 3-5° to the horizontal line, and is placed on a bracket through a rotating bearing. In some more preferred implementation cases, a feed port is provided at a lower horizontal end of the kiln body, and a discharge port is provided at a higher horizontal end of the kiln body; the water flow direction of the segmented water cooling component is opposite to the material flow direction in the kiln body. The cooling water moves downward from top to bottom in a spiral on the horizontal reference system, while the direction of the pre-burned material balls is opposite, so the spiral guide plate is arranged in a counter-spiral relative to the cooling water of the preheating pipe section and the heating pipe section coiled outside the kiln body.
[0067] In some more preferred implementation cases, the segmented water-cooling component includes a preheating pipe section and a heating pipe section according to the horizontal position of the kiln body from high to low; the preheating pipe section is provided with a water inlet, which is connected to the steam generator through a water inlet pipe; the heating pipe section is provided with a water outlet connected to the steam generator.
[0068] In some more preferred implementation cases, the cross-sections of the preheating pipe section and the heating pipe section are semicircular.
[0069] In some more preferred implementation cases, the diameter ratio of the preheating pipe section to the heating pipe section is 1.5-2:1, and the winding number ratio per unit kiln length is 2-3 turns per 10 cm. The above design ratio is to increase the water flow rate in the pipeline and improve its heat exchange effect.
[0070] In some more preferred implementation cases, the diameter of the heating pipe section decreases along the direction of water flow.
[0071] In some more preferred implementation cases, the triple heat exchange and concentrating device includes a first heat exchange and concentrating device, a second heat exchange and concentrating device and a third heat exchange and concentrating device connected in series in sequence; each heat exchange and concentrating device includes a vertical wastewater container and a steam chamber wrapped around the outside of the wastewater container; the top and bottom of the wastewater container are respectively provided with a wastewater inlet and a wastewater outlet; the top of the steam chamber is provided with a steam inlet and a condensed water outlet, and the bottom is provided with a steam outlet; the wastewater outlet of the previous heat concentrating device is connected to the wastewater inlet of the next heat concentrating device; the steam outlet and the condensed water outlet of the previous heat concentrating device are connected to the steam inlet of the next heat concentrating device.
[0072] Specific Examples and Comparative Examples Example 1 (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5.4:1, the iron oxide and strontium carbonate are mixed by a plowshare machine and then introduced into a dry ball mill for ball milling to obtain a dense material after 60 minutes of densification.
[0073] (b) The dense material is passed into a pelletizing plate, and a strontium chloride recovery solution having a mass concentration of 18%, a temperature of 45° C., and a pH of 7 is sprayed through a spray pipe to form pellets to obtain pellets; the moisture content of the pellets is 12wt%.
[0074] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 20%, an air flow rate of 7 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0075] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0076] Combination Figure 1 , Figure 5 and Figure 6 As shown, the preparation method of the strontium chloride recovery solution is: (b-1) One volume of production wastewater with a mass concentration of 3% strontium chloride is introduced into the wastewater volume chamber 3-1 of the first heat exchange and concentration device 3, and concentrated to 0.5 volume by evaporation to obtain a concentrated liquid A and a second steam (the concentrated liquid A is discharged from the wastewater outlet 3-4); the first heat exchange and concentration device 3 is heated by the first steam, and the first steam is heated by the heat exchange kiln 1 in step (c), specifically, the hot water of the heat exchange kiln 1 enters the steam generator 2 to generate steam, and the steam enters the steam chamber 3-2 from the steam inlet 3-5 to heat the wastewater volume chamber 3-1; the temperature of the first steam is 120°C, and the temperature of the second steam is 95°C; the impurity metal content of the production wastewater is 0.12%.
[0077] (b-2) The concentrated liquid A is introduced into the wastewater chamber of the second heat exchange and concentrating device 4. The second heat exchange and concentrating device 4 is heated by the second steam. Specifically, the hot water in the wastewater chamber 3-1 of the first heat exchange and concentrating device 3 flows out of the condensed water outlet 3-6 and mixes with the steam flowing out of the steam outlet 3-7. The hot water and the steam enter the steam chamber 3-2 of the second heat exchange and concentrating device together. After the concentrated liquid A is concentrated to 0.25 volume, the concentrated liquid B and the third steam are obtained. The temperature of the third steam is 75°C.
[0078] (b-3) The concentrated liquid B is introduced into the wastewater chamber of the third heat exchange and concentrating device 5. The third heat exchange and concentrating device 5 is heated by the third steam. Specifically, the hot water in the wastewater chamber 3-1 of the second heat exchange and concentrating device 3 flows out of the condensate outlet 3-6 and mixes with the steam flowing out of the steam outlet 3-7, and then enters the steam chamber 3-2 of the third heat exchange and concentrating device together, and the concentrated liquid B is concentrated to a strontium chloride solution with a mass concentration of 18%, thereby obtaining a strontium chloride recovery solution; the impurity metal content of the strontium chloride recovery solution is 0.16%.
[0079] In step (c), combining Figure 2-4As shown, the heat exchange kiln 1 comprises a kiln body 1-3 which is placed on a bracket 1-2 at an angle of 4° with the horizontal line through a rotating bearing 1-1, a spiral material guide plate 1-3-1 is arranged in the kiln body 1-3, a material inlet 1-4 is arranged at a lower end of the kiln body 1-3 at a horizontal position, and a material outlet 1-5 is arranged at a higher end of the kiln body 1-3 at a horizontal position, and a segmented water cooling component 1-6 is fixedly wound around the outer surface of the kiln body 1-3, and the segmented water cooling component 1-6 comprises a connected preheating pipe section 1-6-1 and a heating pipe section 1-6-2 which are wound around the outer side of the kiln body 1-3 according to the horizontal position of the kiln body from high to low, and the preheating pipe section 1-6-1 and the heating pipe section 1-6-2 are wound around the outer side of the kiln body 1-3 from high to low. The hot pipe section 1-6-1 is provided with a water inlet 1-6-3, and the water inlet 1-6-3 is connected to the steam generator 2 through the water inlet pipe 1-6-4; the steam generator 2 is connected to the first heat exchange and concentration device 1 of step (b-1); the basic structural principles of the first heat exchange and concentration device 3, the second heat exchange and concentration device 4, and the third heat exchange and concentration device 5 are similar; the cross-section of the preheating pipe section 1-6-1 and the heating pipe section 1-6-2 is semicircular; the pipe diameter ratio of the preheating pipe section 1-6-1 and the heating pipe section 1-6-2 is 1.5:1, and the coiling number ratio per unit kiln body length is 10cm2 turns. In the segmented water-cooling component 1-6, the heating pipe section 1-6-2 is closely arranged with a reduced diameter along the water flow direction in order to improve the heat exchange efficiency. The cooling water moves downward in a spiral from top to bottom in the horizontal reference system, while the direction of the pre-burned balls is opposite. Therefore, the spiral guide plate 1-3-1 is arranged in a counter-spiral relative to the preheating pipe section 1-6-1 and the heating pipe section 1-6-2 that are coiled around the outside of the kiln body. After the pre-burned balls are cooled, they enter the next process from the outlet.
[0080] Example 2 The difference from Example 1 is that the molar ratio of iron to strontium in the feed is different, which is 5:1; and the concentration of the strontium chloride recovery solution is different, which is 22%. The specific steps are as follows: (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5:1, the iron oxide and strontium carbonate are mixed by a plowshare machine and then introduced into a dry ball mill for densification, and a dense material is obtained after densification for 60 minutes.
[0081] (b) The dense material is passed into a pelletizing plate, and a strontium chloride recovery solution having a mass concentration of 22%, a temperature of 45° C., and a pH of 7 is sprayed through a spray pipe to form pellets to obtain pellets; the moisture content of the pellets is 12wt%.
[0082] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 20%, an air flow rate of 7 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0083] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0084] Example 3 The difference from Example 1 is that the molar ratio of iron to strontium in the feed is different, which is 5.8:1; and the concentration of the strontium chloride recovery solution is different, which is 16%. The specific steps are as follows: (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5.8:1, the iron oxide and strontium carbonate are mixed by a plowshare machine and then introduced into a dry ball mill for densification, and a dense material is obtained after densification for 60 minutes.
[0085] (b) The dense material is passed into a pelletizing plate, and a strontium chloride recovery solution having a mass concentration of 16%, a temperature of 45° C., and a pH of 7 is sprayed through a spray pipe to form pellets to obtain pellets; the moisture content of the pellets is 12wt%.
[0086] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 20%, an air flow rate of 7 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0087] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0088] Example 4 The difference from Example 1 is that the pH of the strontium chloride recovery solution is different, which is 8. The specific steps are as follows: (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5.4:1, the iron oxide and strontium carbonate are mixed by a plowshare machine and then introduced into a dry ball mill for ball milling to obtain a dense material after 60 minutes of densification.
[0089] (b) The dense material is passed into a pelletizing plate, and a strontium chloride recovery solution having a mass concentration of 18%, a temperature of 45° C., and a pH of 8 is sprayed through a spray pipe to form pellets to obtain pellets; the moisture content of the pellets is 12wt%.
[0090] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 20%, an air flow rate of 7 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0091] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0092] Example 5 The difference from Example 1 is that the sintering conditions are different: the pre-burning oxygen concentration is 16%, and the air speed is 8m / s. The specific steps are as follows: (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5.4:1, the iron oxide and strontium carbonate are mixed by a plowshare machine and then introduced into a dry ball mill for ball milling to obtain a dense material after 60 minutes of densification.
[0093] (b) The dense material is passed into a pelletizing plate, and a strontium chloride recovery solution having a mass concentration of 18%, a temperature of 45° C., and a pH of 7 is sprayed through a spray pipe to form pellets to obtain pellets; the moisture content of the pellets is 12wt%.
[0094] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 16%, an air flow rate of 8 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0095] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0096] Example 6 The difference from Example 1 is that the sintering conditions are different: the pre-burning oxygen concentration is 22%, and the air speed is 5 m / s. The specific steps are as follows: (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5.4:1, the iron oxide and strontium carbonate are mixed by a plowshare machine and then introduced into a dry ball mill for ball milling to obtain a dense material after 60 minutes of densification.
[0097] (b) The dense material is passed into a pelletizing plate, and a strontium chloride recovery solution having a mass concentration of 18%, a temperature of 45° C., and a pH of 7 is sprayed through a spray pipe to form pellets to obtain pellets; the moisture content of the pellets is 12wt%.
[0098] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 22%, an air flow rate of 5 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0099] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0100] Example 7 The difference from Example 1 is that the strontium chloride content of the waste water is 2.2%, the impurity metal content is 0.03%, and the impurity metal content of the strontium chloride recovery solution is 0.09%.
[0101] Example 8 The difference from Example 1 is that the strontium chloride content of the waste water is 4.7%, the impurity metal content is 0.10%, and the impurity metal content of the strontium chloride recovery solution is 0.18%.
[0102] Example 9 The difference from Example 1 is that the pre-sintered pellet temperature is 900°C, the first steam temperature is 110°C, the second steam temperature is 90°C, and the third steam temperature is 70°C.
[0103] Example 10 The difference from Example 1 is that the pre-sintered pellet temperature is 1100°C, the first steam temperature is 125°C, the second steam temperature is 98°C, and the third steam temperature is 76°C.
[0104] Comparative Example 1 The difference from Example 1 is that a conventional manufacturing process is used: strontium chloride is directly added to the pelletizing process according to the proportion. The specific steps are as follows: (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5.4:1, and strontium chloride is added in an amount of about 2.16% of the total mass of iron oxide and strontium carbonate. The iron oxide, strontium carbonate and strontium chloride are mixed by a plowshare machine and then introduced into a dry ball mill for ball milling to obtain a dense material after 60 minutes of densification.
[0105] (b) The dense material is passed into a ball-forming plate to form balls, thereby obtaining ball materials; the moisture content of the ball materials is 12 wt %.
[0106] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 20%, an air flow rate of 7 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0107] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0108] Comparative Example 2 The difference from Example 1 is that the production wastewater is directly used to make pellets. The specific steps are as follows: (a) Iron oxide with a mass purity of more than 98.5% and strontium carbonate with a mass purity of more than 97.5% are prepared at an iron / strontium molar ratio of 5.4:1, the iron oxide and strontium carbonate are mixed by a plowshare machine and then introduced into a dry ball mill for ball milling to obtain a dense material after 60 minutes of densification.
[0109] (b) The dense material is passed into a pelletizing plate, and the production wastewater clear liquid (i.e., the wastewater clear liquid before concentration and recovery in Example 1) is sprayed through a spray pipe to form pellets to obtain pellets; the moisture content of the pellets is 12 wt %.
[0110] (c) The balls are introduced into a rotary kiln and sintered for 90 minutes at an oxygen concentration of 20%, an air flow rate of 7 m / s and a temperature of 1150° C. to obtain pre-fired balls at a temperature of 1000° C. The pre-fired balls are cooled by heat exchange with cooling water in a heat exchange kiln and then introduced into a dry ball mill for crushing to obtain coarse powder with an average particle size of 5.5 μm.
[0111] (d) Wet-milling the coarse powder to an average particle size of 1.5 μm to obtain a slurry; after filtering and drying the slurry, tempering at 900° C. and cooling the slurry to obtain bonded permanent ferrite magnetic powder. The ball-to-water mass ratio of the wet-milling process is 10:1:1.2; the water content after filtering is 19%, and the water content after drying is less than 0.6%.
[0112] Comparative Example 3 The difference from Example 1 is that the concentration of the strontium chloride recovery solution is 25%.
[0113] Comparative Example 4 The difference from Example 1 is that the concentration of the strontium chloride recovery solution is 12%.
[0114] Comparative Example 5 The difference from Example 1 is that the moisture content of the ball material after ball making is 18%.
[0115] Comparative Example 6 The difference from Example 1 is that the moisture content of the ball material after ball making is 9%.
[0116] Comparative Example 7 The difference from Example 1 is that the pH of the strontium chloride recovery solution is 10.0 and the temperature is 60°C.
[0117] Comparative Example 8 The difference from Example 1 is that during the pre-firing process, the oxygen content in the rotary kiln is 15% and the air flow rate is 4 m / s.
[0118] Comparative Example 9 The difference from Example 1 is that the pre-sintered pellet temperature is 800°C, the first steam temperature is 100°C, the second steam temperature is 82°C, and the third steam temperature is 65°C.
[0119] Comparative Example 10 The difference from Example 1 is that the strontium chloride content of the production wastewater is 1.5%, the impurity metal content of the solution is 0.22%, and the impurity metal content of the strontium chloride solution after recovery is 0.31%.
[0120] Performance testing: (1) Average particle size: Use WLP-205A Fisher average particle size analyzer to test the average particle size of magnetic powder before and after tempering. The tempering process is: 850℃ for 30 minutes. Tempering can eliminate some lattice defects and promote the growth of some ultrafine grains, thereby improving overall performance.
[0121] (2) Compression density: The density is calculated by compressing equal weight of magnetic powder to 30 MPa using a carbide die and then measuring the height.
[0122] (3) Rubber mixing: Mix the magnetic powder, rubber binder and additives in the same proportion and then mix and roll them on an open rubber mixer. The roller temperature is 85℃ and the roller spacing is adjusted to 2mm. Mix for 5 minutes to produce a 2mm rubber sheet.
[0123] After cooling to room temperature for 15 minutes, put it in a 60℃ constant temperature box and keep it warm for 1 hour. Fold it 3 times in a calender to produce a 2mm film. The calender roller temperature is 45℃ and the roller spacing is adjusted to 2mm.
[0124] (4) Film magnetic property test: After the film is cooled to room temperature, it is transferred to the test room, which is kept at a constant temperature of 20-23°C. After being left for 60 minutes, five Φ25.4 mm discs are punched out and stacked into a 10 mm thick sample block for performance testing.
[0125] The samples of each embodiment and comparative example 1 were tested, and the results are shown in Table 1.
[0126] Table 1 By comparing the data recorded in the above table, we can see that: The performance of the samples obtained in Examples 1-10 can reach or even exceed the performance of the samples obtained in the conventional process (ie, Comparative Example 1). However, since strontium chloride is recovered from wastewater in Examples 1-10, the cost can be saved by 3-5% in view of the current price of strontium.
[0127] The difference between Comparative Example 2 and Example 1 is that production wastewater is directly used for pelletizing. The production wastewater has poor component stability and low strontium chloride concentration. After being used for pelletizing, the performance of the finished product will fluctuate greatly during the production process. In addition, the iron-strontium molar ratio is too high due to the low strontium chloride concentration in the ball material, resulting in low intrinsic and residual magnetism of the film. Comparative Example 4 also has poor performance due to the low strontium chloride concentration in the ball material, which leads to a high iron-strontium molar ratio. The difference between Comparative Example 6 and Example 1 is that the moisture content of the ball material after pelletizing is 9%, which is a high iron-strontium molar ratio formula. In addition, the low moisture content leads to a loose structure of the ball material, which is dried too quickly after entering the kiln and is easy to collapse, resulting in large performance fluctuations.
[0128] The difference between Comparative Example 3 and Example 1 is that the concentration of the strontium chloride recovery solution is 25%, which results in a too low iron-strontium molar ratio, resulting in a low film remanence Br but a high coercive force Hcj; the difference between Comparative Example 5 and Example 1 is that the moisture content of the ball material after ball making is 18%, which is also a low molar ratio formula, and will affect the pre-firing process, resulting in too low temperature at the tail end of the kiln and increased gas consumption, and is therefore not compatible with the current pre-firing process.
[0129] The difference between Comparative Example 7 and Example 1 is that the pH of the strontium chloride recovery solution is 10.0 and the temperature is 60°C. The temperature of the strontium chloride recovery solution in Comparative Example 7 is too high, and the strength of the ball material is reduced. Analysis shows that the reason may be due to the decrease in water viscosity or too fast evaporation; the pH is too high, and the free strontium ions and calcium ions in the strontium chloride recovery solution are reduced, making the iron strontium molar ratio slightly higher, and the material reacted in the crushing of step (c) and the fine grinding of step (d) is too viscous, making it difficult to evenly disperse the material, and the orientation degree in the magnetic field is reduced, resulting in poor detection performance.
[0130] The difference between Comparative Example 8 and Example 1 is that during the pre-firing process, the oxygen content in the rotary kiln is 15% and the air flow rate is 4 m / s, that is, the solid phase reaction is in a relatively oxygen-deficient environment, and the formation of an ideal ferrite phase requires a sufficient oxygen environment, otherwise it may lead to an increase in side reactions and a significant decrease in the coercive force Hcj.
[0131] The difference between Comparative Example 9 and Example 1 is that the pre-burned ball temperature is 800°C, the first steam temperature is 100°C, the second steam temperature is 82°C, and the third steam temperature is 65°C. This comparative example mainly affects the efficiency of strontium chloride recovery. As long as the concentration, temperature and pH of the sprayed strontium chloride recovery solution are guaranteed, theoretically, it has little effect on the performance. However, production is a system problem. The low temperature of the pre-burned balls will lead to a decrease in the subsequent concentration efficiency, which may cause unstable feeding in continuous production. Unstable feeding in the kiln will cause large fluctuations in performance, and the performance is difficult to predict; the performance of Comparative Example 9, that is, the negative impact on production, is manifested as over-burning of the pre-burned balls and reduced intrinsic properties.
[0132] The difference between Comparative Example 10 and Example 1 is that the strontium chloride content of the production wastewater is 1.5%, the impurity metal content of the solution is 0.22%, and the impurity metal content of the strontium chloride solution after recovery is 0.31%. The strontium chloride recovery solution obtained in Comparative Example 10 is not diluted with a high-concentration strontium chloride solution, so the impurity content is high, while the strontium chloride concentration is low, the iron-strontium molar ratio is high, but the impurity ions are also more, so the intrinsic is slightly better than that of Comparative Example 2, and the remanence is lower.
[0133] In summary, in view of the main purpose of cost saving, the various parameters of this solution are interrelated in production. Adjustment of parameters without subsequent process correction will lead to deterioration of product stability and performance indicators.
[0134] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0135] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a bonded permanent ferrite, characterized in that include: a) densifying red iron oxide and strontium carbonate to obtain a dense material; b) pelletizing the dense material under the condition of spraying strontium chloride recovery solution to obtain ball material; wherein the concentration of strontium chloride recovery solution is 16-22wt%, pH=7-9, and the temperature is 25-50°C; c) Sintering the ball material to obtain pre-burned ball material; the pre-burned ball material exchanges heat with cooling water in a heat exchange kiln and is crushed to obtain coarse powder; d) The coarse powder is wet-ball-milled, filter-pressed, dried, tempered and cooled to obtain bonded permanent ferrite.
2. The preparation method according to claim 1, characterized in that: In step a), The molar ratio of iron to strontium in the iron oxide red and strontium carbonate is 5.0-5.8:1; The densification treatment is to mix iron oxide red and strontium carbonate and then perform dry ball milling to densify the mixture, and the densification time is 30-120 minutes.
3. The preparation method according to claim 1, characterized in that: In step b), The moisture content of the ball material is 10-15wt%; The diameter of the ball material is 8-20 mm, and the volume difference of the ball material does not exceed 20%.
4. The preparation method according to claim 1, characterized in that: In step b), the preparation method of the strontium chloride recovery solution is: 1) Wastewater containing 2-4wt% strontium chloride is concentrated to 40-60% volume by first steam at 100-130°C to obtain concentrated liquid A and second steam at 80-100°C; 2) The concentrated liquid A is concentrated to 20-30% volume by the second steam to obtain the concentrated liquid B and the third steam at 70-80°C; 3) The concentrated liquid B is concentrated by the third steam to a strontium chloride concentration of 16-22 wt %, to obtain a strontium chloride recovery solution.
5. The preparation method according to claim 4, characterized in that: The impurity metal content in the wastewater containing 2-4wt% strontium chloride is less than 0.2wt%; The impurity metal content in the strontium chloride recovery solution is less than 2wt%.
6. The preparation method according to claim 4, characterized in that: Step 1) is carried out in a first heat exchange and concentration device, the first heat exchange and concentration device is heated by first steam, and the first steam is obtained by heat exchange with cooling water in step c); Step 2) is carried out in a second heat exchange and concentration device, and the second heat exchange and concentration device is heated by the second steam; Step 3) is carried out in a third heat exchange and concentration device, and the third heat exchange and concentration device is heated by the third steam.
7. The preparation method according to claim 1, characterized in that: In step c), The sintering conditions are: oxygen concentration 16-22%, air flow rate 5-8m / s, temperature 1100-1200°C, time 60-120min; The temperature of the pre-sintered balls is 800-1000°C.
8. The preparation method according to claim 1, characterized in that: In step c), the average particle size of the coarse powder is 2.0-8.0 μm.
9. The preparation method according to claim 1, characterized in that: In step d), The ball-to-material-water mass ratio of the wet ball milling is 6-10:1:1-1.5; The average particle size of the coarse powder after wet ball milling is 1.0-2.0 μm.
10. The preparation method according to claim 1, characterized in that: In step d), The moisture content of the material after filtration is 15-25wt%, and the moisture content of the material after drying is <0.6wt%; The tempering temperature is 850-950°C.
Citation Information
Patent Citations
Novel method for separating strontium carbonate waste slag acid leaching slurry
CN101838006A
Method for preparing permanent-magnet ferrite pre-sintered material
CN105036721A
Bonding ferrite magnetic powder for calendaring molding as well as preparation method and application of bonding ferrite magnetic powder
CN116768278A
Ferrite magnetic powder for injection molding and preparation method and application thereof
CN118637899A
Method for manufacturing ferrite magnetic powder and ferrite magnet
JP2001110619A